Disaster Risk Reduction Management Plan of Secondary Schools in Sta. Barbara, Philippines - Shielmyn Kate J Manuel; Reynaldo T Gelido (ASEAN Multidisciplinary Research Journal, 2021)
This study was conducted to determine the status of the disaster risk reduction management plan of secondary schools in Sta. Barbara, Pangasinan. Specifically, it looked into the profile of the technical working group (TWG) of school DRRM in terms of their sex, highest educational attainment, years of experience in the program, length of service, and trainings attended related to DRRM.  Likewise, the study assessed the status of DRRM program in terms of the extent of compliance and level of implementation of school to the Philippine Disaster Risk Reduction and Management Plan (RA 10121). These factors were correlated to the profile of the TWG to test their significance to each other. Descriptive design was used in the study. The statistics used in the analysis of data were frequency counts, percentage distribution, average weighted mean (AWM) and Pearson-r. Results revealed that the respondents manifest diverse socio-demographic characteristics as their profile. The extent of compliance to RA 10121 and the level of implementation of RA 10121 of the secondary schools in Sta. Barbara, Pangasinan as perceived by the respondents were seen Highly Compliant and Highly Implemented. There was no relationship between the profile of the respondents and their perceived extent of compliance to RA 10121. Only length of service was found to be significant to the level of implementation of RA10121. It is recommended that schools should appoint members on the TWG those teachers who are most experienced in the school and should be sent to trainings related to DRRM.